Plant-based diet for obesity treatment - Ahmad, Siti Rohaiza (Frontiers in Nutrition, 2022)
Obesity rates continue to rise, resulting in a global epidemic that shows no sign of slowing down. Our understanding of this complex disease is also constantly evolving, requiring health care providers to stay up to date with best practices. The application of Plant-Based Diets (PBDs) may hold the key to a successful weight-control strategy. PBD refers to any dietary pattern that emphasizes the consumption of plant foods while excluding the consumption of most or all animal products. The purpose of this mini-review is to report on the application of PBDs as a potential treatment for obesity. PBDs have also been shown to be beneficial in the treatment of other non-communicable diseases, including the prevention and treatment of type 2 diabetes. Many of the reported RCTs were of short duration. Longer-term studies, as well as studies focusing on strict adherence to the PBD regime, are needed. PBD is a beneficial approach to improving health, particularly in obese patients. Benefits include weight loss, improved cardiovascular health, lower blood pressure, and improved glucose metabolism.